(untitled) (Revista Brasileira Multidisciplinar, 2025)
Due to its significance, a critical summary of the publication ’Selos de cursos de instrução’ (‘Instructional training stamps’) from 1975, issued by the Planning Office of the Regional Directorate of Bauru/SP (the only existing publication on these stamps), will be presented. Additionally, a sample of these stamps will be examined, allowing the presentation of various supplementary features, including some varieties along with their reasons and frequency of occurrence. It was observed that there are stamps with ten different values (0.10, 0.20, 0.30, 0.40, 0.50, 0.70, 0.80, 1.00, 2.00, and 2.50), but for the denomination 0.50 there are two distinct types. Due to the absence of margins on the sheets, the stamps on the sides do not have all edges perforated, resulting in a series of primary permanent varieties (occurring on all sheets). There are four different base sizes for the stamps, with the main one measuring 35 mm x 30 mm. Four types have comb perforation, while the others have mostly rotary mixed perforation, usually 10 ¾ x 10 ½. All sheets have the phenomenon of têche-bêches pairs on the stamps in the two central rows, where the stamps appear as inverted pairs, either joined at the top or at the bottom, depending on each type. In all sheets, the phenomenon of flawed cliché joins occurs due to irregularities in the placement of the reticulated background matrix. These stamps played a significant role in Brazilian philatelic and postal history, having been used by ECT in its internal training for over 30 years. This work contributes to the state of the art in understanding these items.